2018
DOI: 10.1002/nau.23874
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and urinary function following anterior lumbar surgery in females

Abstract: Aims Anterior lumbar interbody fusion procedures (ALIF) and total disc replacement (TDR) with anterior exposure of the lumbar spine entail a risk of a vascular injury and dysfunction of the sympathetic and parasympathetic nerves due to disturbance of the inferior and superior hypogastric plexus. While retrograde ejaculation is a known complication of the anterior spinal approach in males, post‐operative sexual as well as urinary function in females has not yet been thoroughly investigated and was hence the aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Additionally, ALIF may require a secondary posterior approach to achieve 360° support, particularly in isthmic spondylolisthesis at L5–S1 [63, 65]. Furthermore, ALIF can result in approach-related complications such as sexual dysfunction, retrograde ejaculation, or urinary incontinence in male patients and vascular injury in all patients [41, 50, 61, 74]. These risks are inherent in an anterior approach to the lumbar spine because of the proximity of the iliac arteries and veins, as well as the sympathetic plexus.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, ALIF may require a secondary posterior approach to achieve 360° support, particularly in isthmic spondylolisthesis at L5–S1 [63, 65]. Furthermore, ALIF can result in approach-related complications such as sexual dysfunction, retrograde ejaculation, or urinary incontinence in male patients and vascular injury in all patients [41, 50, 61, 74]. These risks are inherent in an anterior approach to the lumbar spine because of the proximity of the iliac arteries and veins, as well as the sympathetic plexus.…”
Section: Resultsmentioning
confidence: 99%
“…46,47 Additional complications after ALIF include retrograde ejaculation, sexual dysfunction, and urinary incontinence. [48][49][50] In contrast, TLIF through a minimally invasive or open approach avoids the morbidity of the transperitoneal ALIF approach but permits the placement of a substantially smaller graft, thereby decreasing the total surface area available for fusion. Dural tears were also more common during TLIF than ALIF in a recent study.…”
Section: Discussionmentioning
confidence: 99%
“…In females, however, a 2019 study after ALIF or TDR showed that patients had improved sexual function at six months postoperatively, and persistent improvements in sexual desire, with no increase in urinary incontinence. The authors proposed that the sexual benefits may be secondary to improvements in pain [17].…”
Section: Sexual Dysfunctionmentioning
confidence: 99%